(untitled) (Journal of Nematode Morphology and Systematics, 2012)
A new species of Chiloplacus, C. tauricus sp. n., is described from moss collected in Crimea, Ukraine. It is characterized by its body 670-895 μm long; lateral field with five incisures; labial probolae bifurcated at one level only, at about one-half or more of their total length, and with an abaxial swelling; cephalic probolae with four tines; single guarding process in primary axils; pharyngeal corpus 3.0-3.9 times isthmus length; excretory pore at metacorpus level; spermatheca 51-78 μm long; postvulval uterine sac 81-115 μm long; sigmoid vagina with a short anterior vulval flap; and vulva pore-like with radially ridged lips. The new species resembles C. tenuis Rashid & Heyns, 1990 by the presence of a guarding process in the primary axils and an abaxial swelling at the base of the labial probolae bifurcation, but differs from it in the number of tines on the lips (4 vs 2) and shape of the vulva, which bears an anterior short vulval flap (vs vulval flap absent).